(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The present study was carried out to study the antimicrobial and antioxidant potential of ethanolic leaf extract of Turnera ulmifolia. The antimicrobial activity was tested against five bacteria. Among the five different bacteria used, in the case of S. typhi the zone of inhibition is higher (30.76 mm) in 40µg/ml concentration followed by 60µg/ml concentration (24.88 mm). In the case of E. coli the zone of inhibition of is higher in 20µg/ml concentration (31.2 mm) In P. aeruginosa also the maximum inhibition zone (20.70 mm) was observed in 20µg/ml concentration followed by 40µg/ml (17.28 mm). At 20µg/ml of concentration the zone of inhibition is higher (18.30 mm) in K. pneumonia .Where as in S. aureus the percentage of inhibition is 10.16 mm in 40µg/ml concentration. The extract was effective on all the five bacteria. The higher percentage of activity in DPPH was observed in 1000µg/ml (94.59%) followed by 800µg/ml (94.28%). More absorbance (0.174) was observed in the concentration of 1000µg/ml followed by 800µg/ml concentration (0.165) in FRAP activity. Antioxidant activity and reducing power of solvent extracts was found to be dose dependent manner.